Veterinary parasitology - Taylor, M. A.; Coop, R. L.; Wall, Richard [ (Richard L.)] (Blackwell Publishing Ltd, 2007)
'Veterinary Parasitology' has been thoroughly revised and restructed to reflect modern teaching practice and this edition offers the most up-to-date coverage of advances in this area, covering parasites from around the world